Analisis Karakteristik Materi Pai Bidang Akidah Akhlak Di Berbagai Jenjang Pendidikan - Noor Syifa Azkia Rahmah; Ghina Sofia Mahfuzah; Aulia Azizatul Hidayah; Hasni Noor (CV. ITTC INDONESIA, 2025)
The rising cases of juvenile delinquency in Indonesia, such as theft, assault, drug abuse, and youth brawls, highlight a growing concern for society, particularly in preserving moral values among the younger generation. As the majority of Indonesians are Muslims, instilling moral values is crucial, one of which is through Islamic Religious Education (PAI). PAI plays a central role in shaping the character, morality, and spirituality of students. The Akidah Akhlak (faith and morality) component in PAI, which addresses the foundation of faith and ethics in daily life, is vital to the success of Islamic education. Akidah Akhlak is taught progressively from Primary School to University levels, with characteristics and approaches adapted to the cognitive, psychological, and social development of students at each level. This study aims to analyze the characteristics of Akidah Akhlak materials across various educational stages, ensuring their alignment with students' developmental needs and contributing to reducing juvenile delinquency. The results show that Akidah Akhlak is systematically designed, focusing on basic faith and good character habits in primary education, expanding on social and moral aspects in secondary education, applying Islamic ethics in society at the senior level, and offering more complex discussions at the university level. The material at each stage aims to produce individuals who are not only intellectually competent but also spiritually strong and morally sound.